Effectiveness of augmented reality learning media in enhancing embedded system programming competence: A 4D development study - Yudistia, Annisa Yumna; Chandra, Oriza (Universitas Jambi, Indonesia, 2025)
This study developed augmented reality (AR)–based learning media for analogue and digital input/output programming using Arduino microcontrollers in the Embedded System Programming course at SMK Negeri 4 Pariaman. The research employed a Research and Development (R&D) approach using the 4D model—Define, Design, Develop, and Disseminate. In the Define stage, the study analysed needs, student characteristics, and curriculum materials. The media was designed, validated by experts, tested for practicality, and examined for effectiveness. Validation results indicated that the media was valid, while practicality tests involving teachers and students showed it was very practical. Effectiveness testing using a paired sample t-test revealed a significant improvement in student learning outcomes (Sig. 0.000 < 0.05; t-count > t-table). N-Gain analysis also demonstrated a high level of learning improvement. Overall, the findings confirmed that the AR-based learning media were feasible, practical, and effective in enhancing students’ understanding of embedded system programming.